Polarization imaging for surface fiber orientation measurements of carbon fiber sheet molding compounds. (January 2023) - Schommer, D.; Duhovic, M.; Hoffmann, T.; Ernst, J.; Schladitz, K.; Moghiseh, A.; Gortner, F.; Hausmann, J.; Mitschang, P.; Steiner, K.
Abstract: The ability to measure the fiber orientation in fiber reinforced polymers plays a vital role in process and part design. Recently, it has been discovered that carbon fibers polarize light, providing an opportunity to detect the fiber orientation in carbon fiber-reinforced polymer parts. The Fraunhofer Institute for Integrated Circuits has developed a polarization camera system capable of measuring the polarization state of light reflected from objects in real-time. In this work, the camera system is used to measure the surface fiber orientation in carbon fiber reinforced Sheet Molding Compound semi-finished products at several stages of the processing chain. First, the fiber orientation of carbon fiber-reinforced Sheet Molding Compound semi-finished product is measured during continuous production, enabling real-time quality control and complete digitization of the material's fiber orientation information. Second, the measurement system is used to characterize static flat pressed carbon fiber reinforced Sheet Molding Compound specimens. In addition, the technique is widely applicable to many other carbon fiber based raw material forms (e.g. preforms, prepregs, tapes) and even composite parts. Graphical abstract: Static and dynamic surface fiber orientation data acquisition and analyses of carbon fiber sheet molding compounds (C-SMCs). Image 1 Highlights: Fiber orientation measurements of carbon fiber sheet molding compounds (C-SMCs) is carried out using polarization imaging. Dynamic fiber orientation data acquisition is demonstrated on a C-SMC semi-finished product production line. Static fiber orientation data acquisition/analyses are shown on C-SMC press rheometry material characterization specimens. The method enables digitalization of the entire C-SMC processing chain.